Tindak Pidana Pencucian Uang Dengan Kejahatan Asal Tindak Pidana Narkoba Pada Putusan Mahkamah Agung RI no. 1303 k/pid.sus/2013 jo. Putusan Pengadilan Tinggi Medan No. 700/pid/2012/pt.mdn jo. Putusan Pengadilan Negeri Medan Nomor 1243/pid.b/2012/pn.mdn - Ferdy Saputra (DE LEGA LATA: JURNAL ILMU HUKUM, 2018)
Money laundering is not only threatening the economic stability and integrity of the financial system, but also harm the joints of the life of society, nation, and state based on Pancasila and the Constitution of the Republic of Indonesia Year 1945 Money laundering is done is to disguise the proceeds of crime. In this case, will be appointed on the crime of narcotics and drugs. Related with the case studies in based on the Supreme Court Decision No. 1303 K / Pid.Sus / 2013 dated August 21, 2013 Jo. High Court Field No. 700 / Pid / 2012 / PT.Mdn dated January 8, 2013 Jo. Medan District Court Decision No. 1243 / Pid.B / 2012 / PN.Mdn dated October 8, 2012 also uses the mode of crimes in the banking field. Mode of crime in the banking sector, in this case, use money transfer services Money Changer (money changers). Predicate crime (crimes origin) it is a criminal offense drug, namely methamphetamine. Methamphetamine trade is carried out between cross country, namely between Malaysia and Indonesia.